Continuability and boundedness of solutions for a kind of nonlinear delay integro-differential equations of third order - Tunç, C.; Ayhan, T. (Нелінійні коливання, 2017)
This paper considers a nonlinear integro-differential equation of third order with delay. We establish sufficient conditions which guarantee the globally existence and boundedness of the solutions of the equation considered. We benefit from the Lyapunov’s second method to prove the main result. An example is also given to illustrate the applicability of our result. The result of this paper is new and improves previously known results. Вивчається нелiнiйне iнтегро-диференцiальне рiвняння третього порядку з запiзненням. Наведено достатнi умови глобального iснування та обмеженостi розв’язкiв розглянутих рiвнянь. Для доведення основного результату використовується другий метод Ляпунова. Також наведено приклад для iлюстрацiї отриманого результату. Отриманий результат є новим та покращує отриманi ранiше результати.